Noncontractible investments and reference points - Oliver Hart (Games, 2013)
We analyze noncontractible investments in a model with shading. A seller can make an investment that affects a buyer's value. The parties have outside options that depend on asset ownership. When shading is not possible and there is no contract renegotiation, an optimum can be achieved by giving the seller the right to make a take-it-or-leave-it offer. However, with shading, such a contract creates deadweight losses. We show that an optimal contract will limit the seller's offers, and possibly create ex post inefficiency. Asset ownership can improve matters even if revelation mechanisms are allowed.
Keywords: 330; incomplete contracts; noncontractible investments; reference points; asset ownership